Effect of specimen size on fracture toughness of mild steel - Mohd Syafiq, Mohd Saufi (2012)
This project was conducted to investigate the effect of specimen size on fracture toughness of mild steel. Fracture toughness is an indication of the amount of stress required to propagate a pre-existing flaw. It is a very important material property since the occurrence of flaws is not completely avoidable in the processing, fabrication, service of a material or component. In this experiment, the specimen size was chosen as a main parameter to analyse the fracture toughness of mild steel. The specimen size was divided into two parameter to be investigated, there is thickness and notch depth of the specimen. The specimen geometry was referred to the ASTM E399-74 standard and the test applied for the fracture toughness is single edge notch bending. From the test results, when the thickness of the specimen increase the fracture decreases until the thickness reach the critical dimension and the fracture was become constant. For the notch depth, when the notch depth decreases the fracture of the specimen also decreases until the notch depth reach the critical dimension and the fracture toughness was become constant. The thickness and notch depth of the specimen is main parameter to analyze the fracture toughness of the material or specimen because each of the specimens will reach the critical dimension and constant the fracture toughness value.